Do worldwide governance drivers affect the blue sustainability practices? an empirical study of the fisheries sector - Alsaleh, Mohd; Yuan, Yuan; Longqi, Sun; Abdul Rahim, A.S. (Springer Science and Business Media B.V., 2023)
The ocean, and the life that dwells in it, is the largest carbon sink of our planet, absorbing more than 25 percent of all CO2 emissions, and over 90 percent of the excess heat generated by humans The ocean, and the life that dwells in it, is the largest carbon sink of our planet, absorbing more than 25 percent of all CO2 emissions, and over 90 percent of the excess heat generated by humans. The task today is for the EU to demonstrate leadership in guiding international ocean governance towards more ocean protection and sustainable management, as the European Green Deal seeks to make the EU a model for marine global sustainability. This paper aims to investigate the dynamic impact of global governance on the sustainability of the fisheries industry in 27 European countries by considering the role of fisheries production and global governance factors over the period 1996–2022. This paper will explore the marine and governance challenges that currently threaten the health of the EU Ocean and living species. The findings showed a substantial positive link between public sector quality, economic growth, economic stability, and the dependent variable fisheries sustainability across all quantiles, and this is achieved by adopting a new method, and this is the Method of Moments Quantile Regression (MMQR) that is in conjunction with fixed factors. Additionally, at the most recent quantiles in the EU27 nations, the impacts of private sector quality and property rights variables on fisheries sustainability were positively significant. However, the effects of individual interest and the sustainability of the fisheries were negatively substantial at the most recent quantiles in the EU27 nations. At the same time, they are having a beneficial, considerable impact on the middle quantiles in EU27 countries, social development, and fisheries sustainability. In particular, the results show that the significant positive effects of economic stability, growth, property rights, public sector quality, and private sector quality on fisheries sustainability are higher in EU13 developing countries than in EU14 developed countries, supporting the growth hypothesis for countries that produce fisheries. Conversely, the findings show that developed EU14 countries have a more significant impact on social development's favorable impact on fisheries sustainability than developing EU13 nations. With the use of effective technology and environmentally responsible investments in the fisheries sector, policymakers may advance marine and ocean governance in the EU14 and EU13 nations and meet sustainable development objectives.